The ‘artificial intelligentsia’ and its discontents: an exploration of 1970s attitudes to the ‘social responsibility of the machine intelligence worker’ - Rosamund Powell; Syed Mustafa Ali; Stephanie Dick; Sarah Dillon; Matthew L. Jones; Jonnie Penn; Richard Staley (BJHS Themes, 2023)
In 1972, ten members of the machine intelligence research community travelled to Lake Como, Italy, for a conference on the ‘social implications of machine intelligence research’. This paper explores their varied and contradictory approaches to this topic. Researchers, including John McCarthy, Donald Michie and Richard Gregory, raised ‘ethical’ questions surrounding their research and actively predicted risks of machine intelligence. At the same time, they delayed any action to mitigate these risks to an uncertain future where technical capabilities were greater. I argue that conference participants’ claims that 1972 was ‘too early’ to speculate on societal impacts of their research were disingenuous, motivated both by threats to funding and by researchers’ own politically informed speculation on the future.